2012
DOI: 10.1007/s00449-012-0692-6
|View full text |Cite
|
Sign up to set email alerts
|

A bioprocess for the production of phytase from Schizophyllum commune: studies of its optimization, profile of fermentation parameters, characterization and stability

Abstract: Schizophyllum commune produces phytase through solid-state fermentation using different agroindustrial residues. After optimization of phytase production, a maximal level of phytase (113.7 Units/gram of dry substrate) was obtained in wheat bran based medium containing 5% sucrose, 50% humidity, 7.5% of biomass at 33 °C pH 7.0 during 72 h and a 285% improvement in enzyme titre was achieved. Analysis of fermentation parameters profile for phytase production showed the highest productivity (1.466 Units/gram of dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 48 publications
6
38
3
Order By: Relevance
“…The studies reported [5][6][7][8][9][10][11] did not reference the recovery of phytase by ultrafiltration and concentration and the data are scarce, so we could not compare them with our results. It seems that the phytase from G. australe G24 is not a b-propeller phytase because b-propeller phytases exhibit both specific Ca 2?…”
Section: Phytase Production Separation and Recovery Stepscontrasting
confidence: 65%
See 1 more Smart Citation
“…The studies reported [5][6][7][8][9][10][11] did not reference the recovery of phytase by ultrafiltration and concentration and the data are scarce, so we could not compare them with our results. It seems that the phytase from G. australe G24 is not a b-propeller phytase because b-propeller phytases exhibit both specific Ca 2?…”
Section: Phytase Production Separation and Recovery Stepscontrasting
confidence: 65%
“…From mushrooms, the studies reported are limited to enzyme activity achieved during cultivation susch as solid state fermentation, for example on the phytases from Grifola frondosa and Lentinus edodes phytases [5], Pleurotus ostreatus Plo 6 phytase [6], and phytases identified from Volvariella volvacea [7], Flammulina velutipes [8], Agrocybe pediades, and Peniophora lycii [9]. Phytases from Schizophyllum commune [10], Grifola frondosa, Lentinula edodes and Ganoderma stipitatum [11] were also found in solid state fermentation (SSF). One challenge for industrial production is to ensure the final consumer product has high viability, activity and a long shelf life.…”
Section: Introductionmentioning
confidence: 99%
“…For the selection of fungal isolate with higher phytase activity using solid state fermentation, inoculum was prepared using mycelial blocks (5×5 mm) from an agar plate of fungal strains on CDA Media at 35 °C for 5 days to inoculate 100 mL of Czapek liquid media [Composition (g/l): sucrose 30, yeast extract 6, KH2PO4 1, MgSO4 0.5, FeSO4 0.01, pH 6.0] in a 250 mL shake flask and incubated at 35 °C and 250 rpm for 5 d in incubator shaker (Salmon et al 2012).…”
Section: Fungal Culture and Inoculum Preparationmentioning
confidence: 99%
“…Penicillium oxalicum has been reported as a promising phytase producing fungi with reports on characterization, heterogeneous expression and engineering of phytase from this fungi are available (Lee et al 2007;Lee et al 2015;Zhao et al 2010). Filamentous fungi have been reported to good sources of phytases with higher production potential than bacteria and can lead to economic production because of their potential to grow on various agro-residues for the production of phytases in SSF (Salmon et al 2012;Singh et al 2015). Filamentous fungi may produce phytase directly on the selected feed/foods in SSF, or crude product may be mixed in feed rations as a value-added supplement (Bogar et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on production of phytase from microorganisms 2, 9–17. However, reports on optimization of the production of high‐activity bacterial phytase by SmF of different agro‐industrial residues are very few.…”
Section: Introductionmentioning
confidence: 99%